This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
   y  = a cos (log x)  + b sin (log x)
x²y = ax² cos (logx)  + b x² sin (log x)
xy  =  ax cos (log x)  +  bx  sin (log x)
Differentiating y two time we get:
dy/dx  =  -a sin (log x) . 1/x  + b cos (log x)  . 1/x
           = 1/x [ -a sin (log x)  + b cos (log x)
d² y/ dx²  = a/x² sin (logx) - a/x² cos (log x)  - b/x² sin (log x)  - b/x² cos (log x)
               = a/x² [ sin (logx) - cos (logx)]  - b/x² [sin logx + cos logx]
x² d²y/dx²  =  a [ sin (logx) - cos (logx)]  - b [sin logx + cos logx]
x²y d²y/dx²  =  a² sin (logx) cos logx - a² cos² (logx)  - ab y cos logx + ab sin² logx
                             - ab cos logx sin logx - b²y sin logx
 xy dy/dx   =  -a² sin logx cos logx + ab cos² logx -ab sin² logx + b² sin logx cos logx
Add the terms in the above two and y, you get answer